HUBUNGAN TOXIC WORKPLACE ENVIRONMENT, OCCUPATIONAL STRESS DAN QUALITY OF WORK LIFE YANG DIMODERASI OLEH ORGANIZATIONAL SUPPORT - Larasati, Nike; Suprayitno, Suprayitno; Susanti, Rina (ITB AAS Indonesia Surakarta, 2024)
Organizations have an important role in managing stress and the quality of work life of their employees, so paying attention to the conditions of the work environment and support from the organization is an important thing to do. However, the facts on the ground show that there are many unpleasant actions in the work environment which eventually lead to a decrease in the quality of work life and the emergence of occupational stress. This study examines the relationship between toxic workplace environment, occupational stress, and quality of work life which is moderated by organizational support. The sample technique used is purposive sampling, with the criteria being that employees working in Indonesia are at least 18 years old with a minimum working period of 1 year. The software used to assist data processing is SMART-PLS with the analysis used is SEM. The results of this study, sampling there is one hypothesis that is supported, namely the Toxic Workplace Environment has a significant positive effect on occupational stress and in this study organizational support cannot moderate the relationship between toxic workplace environment, occupational stress, quality of work life Keywords : toxic workplace environment, occupational stress, quality of work life, organizational support